2014
DOI: 10.1007/s00421-014-3072-x
|View full text |Cite
|
Sign up to set email alerts
|

Shoe drop has opposite influence on running pattern when running overground or on a treadmill

Abstract: Shoe drop appears to be a key parameter influencing running pattern, but its effects on vGRF differ depending on the task (treadmill vs. overground running) and must be considered with caution. Unlike shod conditions, kinematics of barefoot condition was not altered by treadmill running explaining opposite conclusions between the tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
5
46
1
Order By: Relevance
“…When participants could not be divided evenly among the effects (e.g., nine participants for two effects), the remaining participant was allocated to the stiffer surface (e.g., concrete) as this best reflects the running environment of recreational runners [1,39] or to the higher running speed to increase statistical power as most studies used relatively slow to moderate speeds. When multiple study effects were reported that were not of direct interest to this review (e.g., separate effects for the left and right leg [19], separate effects for heel-strike and non-heel-strike runners [40], and separate effects for shoes with different rearfoot midsole thicknesses [41]), a combined effect was computed across these outcome measures as detailed by Borenstein et al [42] for dependent continuous outcomes. One study reported separate effects for males and females [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When participants could not be divided evenly among the effects (e.g., nine participants for two effects), the remaining participant was allocated to the stiffer surface (e.g., concrete) as this best reflects the running environment of recreational runners [1,39] or to the higher running speed to increase statistical power as most studies used relatively slow to moderate speeds. When multiple study effects were reported that were not of direct interest to this review (e.g., separate effects for the left and right leg [19], separate effects for heel-strike and non-heel-strike runners [40], and separate effects for shoes with different rearfoot midsole thicknesses [41]), a combined effect was computed across these outcome measures as detailed by Borenstein et al [42] for dependent continuous outcomes. One study reported separate effects for males and females [13].…”
Section: Discussionmentioning
confidence: 99%
“…Second, this review was restricted to non-incline, shod, non-fatigued motorized MT and constant-velocity running below 25 km/h in healthy adults. Biomechanical differences are likely larger when accelerating [100,101] and when running at higher speeds (i.e., sprinting) on regular MT's [17,21] and may also be impacted by the use of shoes [41] and fatigue status [57,58] and the findings of this review can therefore not be generalized to these conditions. Indeed, special MTs have been developed for sprinting that may reduce biomechanical differences [102][103][104].…”
Section: Limitations and Future Directionsmentioning
confidence: 92%
“…The incremental test was always performed first, and both submaximal running tests were performed in a random order. All sessions were performed at the same day period to avoid any circadian rhythm effects (Atkinson and Reilly 1996), and overground to be as close as possible to an ecological and a realistic running session (Saunders et al 2004;Chambon et al 2015;Barnes and Kilding 2015).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…For injury prevention, most of the positive biomechanical changes attributed to barefoot running pattern would result from the adoption of a forefoot contact and reduced impact peak (Hall, Barton, Jones, & Morrissey, 2013;Paquette, Zhang, & Baumgartner, 2013). On the other hand, barefoot overground running would lead to increased loading rate (Chambon, Delattre, Guéguen, Berton, & Rao, 2015) and minimalist shoes to a greater incidence of foot stress injuries in newly "minimalist" runners (Ridge et al, 2013). No definitive conclusions can thus be drawn, even in the absence of fatigue, regarding specific risks or benefits to running barefoot, shod or in minimalist shoes (Perkins, Hanney, & Rothschild, 2014).…”
Section: Introductionmentioning
confidence: 97%